Trends of nitrogen oxides in ambient air in nine European cities between 1999 and 2010. (September 2015) - Henschel, Susann; Le Tertre, Alain; Atkinson, Richard W.; Querol, Xavier; Pandolfi, Marco; Zeka, Ariana; Haluza, Daniela; Analitis, Antonis; Katsouyanni, Klea; Bouland, Catherine; Pascal, Mathilde; Medina, Sylvia; et al.
Abstract: Legislation controlling vehicle emissions has been credited with a general downward trend in NOx (NO2 +NO) concentrations in Europe since the 1990's. However, recent studies suggest that traffic (roadside) (TR) NO2 concentrations have not decreased as expected, and in some cases increased, most likely due to the use of oxidation catalysts and particle filters in diesel vehicles (EURO III, IV, V, VI). In this study we describe the time trends in NOx, NO2 and NO concentrations in 9 European cities comparing TR and urban background (UB) monitoring locations. In each city, we collected hourly city-specific NOx, NO, and NO2 data from one TR and one UB monitoring site for each year. We describe hourly, weekly, seasonal and inter-annual patterns for periods corresponding to the implementation dates of various EURO vehicle emission standards regulating NOx emissions. The diurnal patterns in all 9 cities strongly reflected morning and evening traffic. In addition, lower weekend concentrations were observed. The NOx concentrations from the TR sites remain unchanged in the majority of the cities over the study period. When stratified by 3 time periods according to the implementation of the EURO standards, an increasing NO2 /NOx ratio in 7/9 cities with time was noted. However, over the same time period the NO/NO2 ratio decreased in 8/9 cities. A permanent inversion of the NO/NO2 ratio was observed to occur in 2003 in 5/9 cities. Our analyses of temporal and diurnal patterns of NOx in European cities show reductions in concentrations consistent with reductions in primary emissions likely arising from the implementation of successive EURO standards. The generally constant or increasing NO2 concentrations in the majority of the cities assessed over the study period underline the need of further regulative measures to meet the air quality standards and consequently to minimise adverse effects on human health. The ongoing collection and analysis of pollution concentrations across the EU is recommended to monitor trends in pollutants associated with adverse health effects. Highlights: Roadside NOx concentrations fell or remain unchanged at the majority of sites. No change or increases in NO2 concentrations at the majority of sites. Roadside NO/NO2 ratio decrease at sites in 8 cities, in 5 cities change in 2003. Trends in NOx consistent with reductions in traffic-related emissions from implementation of EURO standards.